An application of improved synchronous reference frame-based voltage sag detection in voltage sag compensation system - Y. Kumsuwan (2018)
This paper proposes an application of improved synchronous reference frame (ISRF)-based voltage sag detection in voltage sag compensation system. The ISRF-based voltage sag detection presents the fast detection time that is suitable to use in voltage sag compensation system. The proposed voltage sag compensation system consists of 1) ISRF-based voltage sag detector, 2) static transfer switches (STSs), and 3) alternative voltage source using the inverter. In a normal incident, the load fed the power from main voltage source via the main STS. When the voltage sag occurs and it is detected by the voltage sag detector, the alternative STS connects the load to an alternative voltage source instead of the main STS. The computer software simulation and the experiment were made to investigate and verify the operation of proposed voltage sag compensation system. It can be seen from the results that a short voltage sag detection time is obtained and voltage sag can be compensated with the proposed system. © 2013 IEEE.